1999
DOI: 10.1038/sj.bmt.1702037
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of chronic myelogenous leukemia with autologous bone marrow transplantation followed by roquinimex

Abstract: Summary:Unmanipulated autologous bone marrow transplant (ABMT) offers patients with chronic myelogenous leukemia (CML) a long-term survival of 10%, at best. Immunotherapy has a role in the myeloid leukemias, and there is increasing evidence that of all hematopoietic neoplasms, CML may be the most susceptible to immune regulation. Roquinimex is known to enhance T cell, NK cell and macrophage activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The histopathology of allogeneic cutaneous GVHD typically includes basal vacuolopathy and degeneration with or without lymphocytic infiltration, but eccrine gland involvement and destruction (as observed in the skin biopsy from one of our study patients) has also been reported especially in the chronic phase of allogeneic GHVD (47). A pattern of eccrine gland GVHD was described previously in patients who received an autologous transplant for CML followed by linomide, an immunomodulatory agent (48). …”
Section: Discussionmentioning
confidence: 78%
“…The histopathology of allogeneic cutaneous GVHD typically includes basal vacuolopathy and degeneration with or without lymphocytic infiltration, but eccrine gland involvement and destruction (as observed in the skin biopsy from one of our study patients) has also been reported especially in the chronic phase of allogeneic GHVD (47). A pattern of eccrine gland GVHD was described previously in patients who received an autologous transplant for CML followed by linomide, an immunomodulatory agent (48). …”
Section: Discussionmentioning
confidence: 78%
“…12 In another study, one patient (of 17) who received roquinimex as post transplant immunotherapy was PCR negative at 33 months of follow-up. 35 Although two of the molecular responses seen in our study occurred early after T-cell infusion and could have been due to the transplant alone, the response which occurred in patient UN-2 was delayed in onset and has been durable features which are more typical of an 'antileukemic' immune-mediated response. Although low-dose interferon alpha was utilized for maintenance therapy, in this patient, the disease was previously refractory to this agent.…”
Section: Discussionmentioning
confidence: 86%
“…Additionally, the NK cell line NK-92 was generated under good manufacturing practices with the purpose of ex vivo purging of CML cells for autografts due to its selective ability to lyse leukemic progenitors [51]. In terms of in vivo administration of activated NK cells, to our knowledge no studies have been conducted in CML patients, however use of NK stimulating agents such as IL-2 [52,53], and roquinimex [54], has been performed with some clinical benefit, although at present these therapies have not been optimized. Despite this, the clinical relevance of NK cells in CML should not be underestimated.…”
Section: Immunogenicity Of Cml: the Innate Immune Responsementioning
confidence: 99%